215k views
5 votes

-2m-5m=9m-12

User Kiran K G
by
5.4k points

2 Answers

3 votes

Answer:


\boxed{ \bold{ \huge{ \boxed{ \sf{m = 0.75}}}}}

Explanation:


\sf{ - 2m - 5m = 9m - 12}

Collect like terms


\sf{ - 7m = 9m - 12}

Move 9m to left hand side and change it's sign


\sf{ - 7m - 9m = - 12}

Collect like terms


\sf{ - 16m = - 12}

Divide both sides of the equation by -16


\sf{ ( - 16m)/( - 16) = ( - 12)/( - 16) }

Calculate


\sf{ m = 0.75}

Hope I helped!

Best regards!!

User Omalave
by
6.4k points
3 votes

Answer:


- 2m - 5m = 9m - 12 \\ ⟶ - 2m - 5m - 9m = - 12 \\ ⟶ - 16m = - 12 \\ ⟶ - m = ( - 12)/(16) \\ ⟶ - m = ( - 6)/(8) \\ ⟶ m = - ( - (6)/(8) ) \\ ⟶m = (6)/(8)


m=0.75

User Sergey Menshov
by
5.5k points